2008
DOI: 10.1177/1049732308322487
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Political Violence: Narrative Inquiry Across a 20-Year Period

Abstract: The study of long-term effects of political violence generally concentrates on effects of a single event or period of violence on individuals or groups of individuals and commonly relies on recollections from those who experienced violence a long time after the event. Against the backdrop of Northern Ireland's Troubles, in this article we use narrative inquiry methodology to explore the long-term effects of violence across a 20-year period on a different level. Using two sets of interview data, one collected 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 39 publications
1
11
0
2
Order By: Relevance
“…Social and health problems continue to reflect the impact of past political conflict on both physical and mental health (Dillenburger, Fargas, & Akhonzada;O'Reilly & Stevenson, 2003). Northern Ireland includes several of the most socially disadvantaged areas of the UK, with high levels of deprivation and unemployment in some areas (Northern Ireland Statistics and Research Agency, 2010).…”
Section: The Context Of Maternity Services In Northern Irelandmentioning
confidence: 99%
“…Social and health problems continue to reflect the impact of past political conflict on both physical and mental health (Dillenburger, Fargas, & Akhonzada;O'Reilly & Stevenson, 2003). Northern Ireland includes several of the most socially disadvantaged areas of the UK, with high levels of deprivation and unemployment in some areas (Northern Ireland Statistics and Research Agency, 2010).…”
Section: The Context Of Maternity Services In Northern Irelandmentioning
confidence: 99%
“…Scholars of political violence in El Salvador and Argentina concluded political violence deliberately destroys relationships, social ties and networks (Martín-Baró et al ., 1994, Robben, 2005). While other authors do not characterize the destruction of networks as an overt act of political violence, studies by Pedersen et al (2008), Jones, et al (2003), and Dillenburger et al (2008) in Peru, Kosovo and Ireland found destruction of networks was the ultimate result.…”
Section: Resultsmentioning
confidence: 91%
“…Massive displacement and migration due to political violence diminishes local and national networks, with scholars estimating the majority of the world’s 12 million refugees and 22 to 25 million internally displaced persons are fleeing political violence (Pedersen, 2002, Sidel and Levy, 2008). Massive displacement, internal and outward migration were reported as consequences of political violence by Dillenburger, et al (2008), Carballo, et al (2004), de Jong, et al (2002), Pedersen, et al (2008), Ugalde, et al (2000), and Jones, et al (2005) in their studies in Ireland, Bosnia, Sri Lanka, Peru, El Salvador and Zimbabwe. Evans-Campbell, et al (2008) concluded forced displacement of American Indian children into boarding schools, adoptions and foster care has lasting consequences for communities, including loss of language and traditional practices and potential future leaders, ultimately jeopardizing the ability of a community to envision or plan its collective future.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations